Laparoscopic cholecystectomy in hepatitis C liver cirrhosis patients: “to drain or not to drain: impact on postoperative pain” - Hassan, Ahmed Mohamed Abdelaziz; Elsebae, Magdy M. A.; Abbas, Mohamed; Ezzat, Hussien; Ali, Mohamed Z.; Ebied, Reeham Said (International Surgery Journal, 2019)
Background: When cirrhotic patients with symptomatic gallstones require laparoscopic cholecystectomy (LC), the drainage tube is supposed to prevent postoperative abdominal radiating to the right shoulder, nausea and vomiting due to pneumoperitoneum using carbon dioxide gas. Aim of this work is to evaluate the effect of placing of drains on the incidence of postoperative pain, nausea and vomiting in those patients. Methods: sixty-four patients with uncomplicated chronic calcular cholecystitis and liver cirrhosis were recruited for the study during the period from February 2017 to February 2019. They electively operated upon at the department of general surgery of Theodor Bilharz Research Institute (TBRI) using laparoscopic technique. Patients were subdivided into two equal groups Group-I (n=32); suction drains were placed in the sub-hepatic region (Morison’s pouch) and Group-II (n=32), no drains were placed. Duration of surgery, postoperative shoulder tip pain and vomiting and analgesics requirement were evaluated and recorded. Results: Operative time’s difference was not statistically significant between the two groups. Drain group had a significant lower shoulder tip pain and analgesic requirement at post-operative 6 and 12 hours but that was higher After 12 hours, than group without drain. The overall incidence of nausea/vomiting was significantly higher statistically in group without drain than in drain group. Patients in drain group had a significantly longer hospital stay as compared to group without drain that was statistically significant. Conclusions: Although the incidence of pain and nausea/vomiting are less in early post-operative period after LC with abdominal drain in hepatitis C liver cirrhosis patients; its routine use is not justified because post-operative pain and analgesic requirement after 12 hours is higher and hospital stay is longer.